ChemInform Abstract: Recent Developments in the Chemistry of Pyridyl‐Functionalized, Low‐Coordinate Phosphorus Heterocycles. Issue 4 (January 2015) - Mueller, Christian; Sklorz, Julian A. W.; de Krom, Iris; Loibl, Antonia; Habicht, Marija; Bruce, Marlene; Pfeifer, Gregor; Wiecko, Jelena
Abstract Review: [53 refs.